Altar, Heart, Title‐Page: The Image of Holy Reading [with illustrations]. (12th September 2013) - Dyck, Paul
Abstract : George Herbert's shaped poem "The Altar" has been read as a contradiction of image and word (the perfect pagan altar of the Greek Anthology versus the broken Christian heart) and as a politically‐charged reminder of Laudian church reforms (invoking the re‐building of stone altars). This essay interprets the poem in light of a more common and arguably more generative referent: the biblical and devotional title‐page. Herbert placed "The Altar" at the beginning of the main part of The Temple, "The Church, " so that it functions as its title‐page. In so starting with a picture of an altar that turns out to be a picture of a heart, Herbert decidedly situates his book of poetry as a serious piece of devotional work, following the models of Bibles and devotional books that feature on their title‐pages either hearts or altars or both (hearts on altars). This essay attends to several of these title‐pages, asking how they speak and what they say about the act of holy reading, and then turns to "The Altar, " asking how it takes up the work of these title‐pages, both transforming their messages and setting out the project of The Temple . (P. D.)